2019
DOI: 10.1109/tnsre.2018.2890272
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Sleep Stage Classification Based on Subthalamic Local Field Potentials

Abstract: Deep brain stimulation (DBS) is an established treatment for patients with Parkinson’s disease (PD). Sleep disorders are common complications of PD and affected by subthalamic DBS treatment. To achieve more precise neuromodulation, chronic sleep monitoring and closed-loop DBS toward sleep-wake cycles could potentially be utilized. Local field potential (LFP) signals that are sensed by the DBS electrode could be processed as primary feedback signals. This is the first study to systematically investigate the sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 46 publications
1
65
0
Order By: Relevance
“…All the LFP signals were sensed differentially through adjacency contacts by implantable pulse generator (IPG) with 1,000 Hz sampling rate. The detailed methods of the LFPs data collection and processing were described in our previous studies ( 14 ). The 10-min data was collected when the stimulation was off at each time.…”
Section: Methodsmentioning
confidence: 99%
“…All the LFP signals were sensed differentially through adjacency contacts by implantable pulse generator (IPG) with 1,000 Hz sampling rate. The detailed methods of the LFPs data collection and processing were described in our previous studies ( 14 ). The 10-min data was collected when the stimulation was off at each time.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this change we also observed combinations of alpha, beta and gamma bands which could be used as chronic biomarkers for the classification of different sleep stages ( Chen et al, 2019 ). The results have guided the development of a closed-loop DBS approach.…”
Section: Neurotechnology and Neuroengineering In Dbs Researchmentioning
confidence: 87%
“…The first clinical trial has been completed in PD patients ( n = 13) with a successful post-surgery follow-up through 12 months. Preliminary data have been used to characterize components of β-band oscillations during sleep states ( 11 ). Furthermore, it is reported that the response of β-band oscillations to high-frequency DBS is changed over time, which is a likely result from changes in neural network plasticity.…”
Section: Some Recent Deep Brain Stimulation Technology Advancementsmentioning
confidence: 99%
“…Future developments toward robust online learning techniques that explore large decision spaces and adapt to feedback in real time are essential to online learning problems. The application of AI techniques may allow us to uncover the mechanisms of DBS and the understanding of how DBS influences brain networks ( 11 ). It is noteworthy that recent advances in MRI-compatible DBS devices are allowing for acquisition of neuroimages during stimulation.…”
Section: Some Recent Deep Brain Stimulation Technology Advancementsmentioning
confidence: 99%